2010
DOI: 10.1021/bm100413w
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Tunable FGF-2 Releasing Polyelectrolyte Multilayers

Abstract: Fibroblast growth factor 2 (FGF-2) is a potent mediator of stem cell differentiation and proliferation. Although FGF-2 has a well-established role in promoting bone tissue formation, flaws in its delivery have limited its clinical utility. Polyelectrolyte multilayer films represent a novel system for FGF-2 delivery that has promise for local, precisely controlled and sustained release of FGF-2 from surfaces of interest including medical implants and tissue engineering scaffolds. In this work, the loading and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 64 publications
4
108
1
1
Order By: Relevance
“…91,92 The release of fibroblast growth factor 2 (FGF-2) has been controlled with the construction of poly (b-aminoester)s/heparin (HEP)/FGF-2/HEP tetralayers deposited on top of PEI/SPS multilayers. 43 This approach was similar to another study using tetralayers for controlled hydrophobic drug and polysaccharide release. 93 The incorporation of the poly (b-aminoester) polymer into the tetramer was to prevent the localized degradation of the PEM due to cellular interactions.…”
Section: Detzel Et Almentioning
confidence: 76%
See 2 more Smart Citations
“…91,92 The release of fibroblast growth factor 2 (FGF-2) has been controlled with the construction of poly (b-aminoester)s/heparin (HEP)/FGF-2/HEP tetralayers deposited on top of PEI/SPS multilayers. 43 This approach was similar to another study using tetralayers for controlled hydrophobic drug and polysaccharide release. 93 The incorporation of the poly (b-aminoester) polymer into the tetramer was to prevent the localized degradation of the PEM due to cellular interactions.…”
Section: Detzel Et Almentioning
confidence: 76%
“…The bioactivity of the released protein was verified through its exposure to preosteoblasts and by monitoring their proliferation. 43 Information on additional studies investigating the delivery of bioactive molecules using PEMs is provided in Table 2, further supporting the versatility of PEMs in stimulating phenotypic maintenance.…”
Section: Detzel Et Almentioning
confidence: 90%
See 1 more Smart Citation
“…34 The obtained multilayers are widely used as controlled-release drug systems without changing their biological function within the coating. [35][36][37][38] Sukhishvili et al have recently reported a coating with a "self-defense" behavior that promotes the release of different dose of antibiotic in function of the decrease of the pH around the surface due to the presence of bacteria. 39 Here, we report, for the first time, polyelectrolyte multilayers films made of poly-(Llysine) and hyaluroanan-aldehyde (PLL/HA-Ald) derivative, which possess the main advantage to form stable structures through an auto-crosslinking mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Cell culture medium consisting of alpha minimum essential medium (␣MEM, Invitrogen, Carlsbad, CA, USA) supplemented with 1% albumin and 1% penicillin/streptomycin based on the method of Macdonald et al (2010) was used as the test medium. One hundred microliters of the cell culture medium was added to each well with a cast SC film containing FGF-2 (2500, 250, or 25 ng/unit) and incubated at 37 • C. The medium was replaced daily with 100 l of flesh medium.…”
Section: Release Properties Of Fgf-2 From Sc Filmsmentioning
confidence: 99%